2021
DOI: 10.1002/aoc.6185
|View full text |Cite
|
Sign up to set email alerts
|

Mononuclear iron(III) complexes derived from tridentate ligands containing non‐innocent phenolato donors: Self‐activated nuclease, protease, and phenoxazinone synthase activity studies

Abstract: The tridentate ligands HPhimpH, OCH3PhimpH, CH3PhimpH, tBuPhimpH, and NO2PhimpH have been synthesized and characterized. These tridentate ligands having non‐innocent phenolato function, Npy and Nim donors upon deprotonation bind to iron(III) center resulting in a series of novel iron complexes, namely, [Fe(HPhimp)2](ClO4) (1), [Fe(OCH3Phimp)2](ClO4) (2), [Fe(CH3Phimp)2](ClO4) (3), [Fe(tBuPhimp)2](ClO4) (4), and [Fe(NO2Phimp)2](ClO4) (5). Complexes were characterized by elemental analysis, IR, and UV–visible, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 83 publications
0
2
0
Order By: Relevance
“…For the chiral PS-b-P4VP/MA inverse micelles containing Fe 3+ ions, an absorption band appeared near 380 nm, corresponding to ligand to metal charge transfer (LMCT) transition (Figure 2a). 43,44 The CD spectra show mirror-imaged CD signals at 400 nm with a g-factor of 4.3 × 10 −4 (Figure 2b). In Figure 2c, the chiral PS-b-P4VP/MA inverse micelles containing Co 2+ ions exhibited a broad absorption band around 650 nm and mirror-symmetric CD peaks at 550 nm, both originating from LMCT and d−d transitions.…”
Section: Procedures For Preparation Of Chiral Metal Oxidementioning
confidence: 99%
“…For the chiral PS-b-P4VP/MA inverse micelles containing Fe 3+ ions, an absorption band appeared near 380 nm, corresponding to ligand to metal charge transfer (LMCT) transition (Figure 2a). 43,44 The CD spectra show mirror-imaged CD signals at 400 nm with a g-factor of 4.3 × 10 −4 (Figure 2b). In Figure 2c, the chiral PS-b-P4VP/MA inverse micelles containing Co 2+ ions exhibited a broad absorption band around 650 nm and mirror-symmetric CD peaks at 550 nm, both originating from LMCT and d−d transitions.…”
Section: Procedures For Preparation Of Chiral Metal Oxidementioning
confidence: 99%
“…[7][8][9][10][11][12][13][14][15] Several studies have reported the catalytic activity of iron complexes for the selective oxidation of o-aminophenols to produce the pharmaceutically important amino-3-H-phenoxazin-3-one (APX) instead of ring-opening. [16][17][18][19][20][21][22][23][24] The current study aims to gain a deeper understanding of the natural process of metal ions as catalysts and gain experience in designing more efficient catalysts. In this respect a strategically constructed ligand system can provide the metal complex desirable properties that enable it to mimic the metalloprotein and this is the basis of the biomimetic chemistry.…”
Section: Introductionmentioning
confidence: 99%